Clinical and etiological features of peadiatric facial neuropathy and their role in predicting outcomes - M. A. Irikova; E. Yu. Skripchenko; V. B. Voitenkov; N. V. Marchenko; N. V. Skripchenko; O. V. Goleva; I. B. Petrov (Журнал инфектологии)
The aim: to characterize the clinical and etiological features of facial palsy (FP) in children of different ages at the present stage and their correlation with the outcome and duration of the disease.Materials and methods: the data of 68 children with FP were obtained. The neurological examination with an assessment of the level of facial nerve damage and the severity of FP using the House-Brackmann scale (HB), the concomitant symptoms and the etiological verification of a possible infectious agent were performed to all children. Also, their correlation with the outcomes and duration of the disease were assessed.Results: in the etiological structure infectious FP are more common in children under 12 years of age, with a predominance of herpesviruses and enteroviruses, whereas, more than half of the cases in children over the age of 12 years are idiopathic (Bell’s palsy), less often herpesviruses. A longer course and the probability of an unfavorable are significantly more often observed in the group of children under 12 years of age. There was also a significant correlation between the severity of FP according to HB with the outcomes and duration of the disease.Conclusion: The results confirm the importance and necessity of laboratory confirmation of a possible etiological agent associated with the development of FP. The severity of FP doesn’t depend on the age of the child, but correlates with the outcome and duration of the disease, more less with the synkinesia. A promising direction for further research is to clarify the climatic factors affecting the incidence of FP.